Geometry Concepts in the Reog Cemandi Sidoarjo Dance as a Learning Resource for Elementary School Mathematics - Divi Indar Rukmana; Feny Rita Fiantika; Susi Hermin Rusminati (Formosa Journal of Sustainable Research, 2023)
This research aims to describe the relationship between mathematics and culture, especially culture in the form of the Reog Cemandi Sidoarjo dance art. The focus of this research is to describe geometric concepts through the Reog Cemandi Sidoarjo dance which can be used as a learning resource in elementary school mathematics learning. This research uses a qualitative method with an ethnographic approach where this approach is used to determine the material of flat shapes in mathematical concepts contained in the properties worn and used by Reog Cemandi Sidoarjo dance performers. The results of this research show that in the Reog Cemandi Sidoarjo dance there are mathematical elements which can be linked to mathematics learning, especially in elementary schools. There are four types of props for the Reog Cemandi Sidoarjo dance which contain geometric concepts, namely wooden machetes, headbands (udeng), yellow sampur, and jarik cloth motifs. The flat shape concepts found are a wooden machete (trapezoid), a headband (triangle), a yellow sampur (rectangle), and a jarik cloth motif (parallelogram). The findings of geometric concepts can be used as a culture-based learning resource for fourth grade elementary school students